2021
DOI: 10.3389/fpsyg.2021.712806
|View full text |Cite
|
Sign up to set email alerts
|

A Counseling Application as an Alternative Tool in Increasing Coping Self-Efficacy Among University Students With Academic Distress During Coronavirus Disease 2019 Pandemic in Indonesia: A Study Protocol for a Randomized Controlled Non-Inferiority Trial

Abstract: The coronavirus disease 2019 (COVID-19) pandemic increased education-related distress among University students globally, including in Indonesia. Psychological factors, such as academic demands, limited opportunity to meet their peers, problematic use of technology, and domestic problems, influenced the well-being of the students, leading to poor academic performance. A mobile-based counseling application was developed to address the distress among University students. The application was meant to reach studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A total of 31 items in the RSUS were rated on a 5-point Likert scale ranging from 1 ("strongly disagree") to 5 ("strongly agree"). There were six dimensions in the RSUS, which were as follows: self-efficacy (SE; item 1-5), self-acceptance (SA; item 6-8), emotional stability (ES; item 9-15), problemsolving (PS; item [16][17][18], support from friends (SFRI; item [19][20][21][22][23][24][25][26] and support from family (SFAM; item [27][28][29][30][31]. The scale SE evaluated the degree to which individuals affirmed their self-competence, and the items were listed such as "I am confident in my abilities" and "if I try, I can do things as well or better than anyone else".…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 31 items in the RSUS were rated on a 5-point Likert scale ranging from 1 ("strongly disagree") to 5 ("strongly agree"). There were six dimensions in the RSUS, which were as follows: self-efficacy (SE; item 1-5), self-acceptance (SA; item 6-8), emotional stability (ES; item 9-15), problemsolving (PS; item [16][17][18], support from friends (SFRI; item [19][20][21][22][23][24][25][26] and support from family (SFAM; item [27][28][29][30][31]. The scale SE evaluated the degree to which individuals affirmed their self-competence, and the items were listed such as "I am confident in my abilities" and "if I try, I can do things as well or better than anyone else".…”
Section: Methodsmentioning
confidence: 99%
“…Remote psychological counseling is the most used means of psychological intervention in the school context. In a sample of 160 Chinese adolescents, an intervention of psychological counseling combined with outdoor exercise proved to have an effect on resilience during the early stage of the COVID-19 pandemic [18]. Combined with a semi structured interview and questionnaire, an Italian study concluded that online counseling intervention inclusive of telephone listening services, paired with psychoeducational workshops in quarantine, could improve the resilience of university students [19].…”
Section: Intervention In Resilience During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation